Effect of long-term fertilization on soil fertility of wheat (Triticum aestivum )-corn (Zea mays ) double cropping system in China - WU, LAN FANG; OUYAN, ZHU (The Indian Journal of Agricultural Sciences, 2011)
A 12-year field trial was carried out during 1990-2001 to evaluate effects of fertilization on soil fertility under continuous wheat (Triticunt aestivunt L. emend.Fiori & Paol.>-corn (Zea mays L.) double cropping system in the North China Plain. Total soil nitrogen of top soil (0-20 cm) increased significantly with time in the treatments with N application, such as NPK, NP and NK treatments and those of subsoil (20-60 cm) were no different in all treatments. The changes of available soil N were very similar under each treatment, which increased before October1996 then decreased with fluctuation. Both total soil P and available soil P of topsoil (0-20 cm) increased markedly with time in the treatments with P application such as NPK, NP and PK, while those in subsoil (20-60 cm) remained relative stable and no signiiicant difference in all treatments. The changes of total soil K fluctuated very much and were similar under each treatment, however, available soil K of topsoil (0-20 cm) increased significantly with time in treatments with K application such as NPK, NK and PK, while decreased slightly in K-omitted treatments, those in subsoil (2060 crn)decreased slightly and showed no distinct differences in all treatments. With time, sol;l organic matter in topsoil (0-20 cm) maintained relative stable and those in 20-60 cm depth soil decreased slightly in all treatments. Balanced use of N, P and K is required to maintain soil fertility.